Pretreatment and process predictors of nonresponse at different stages of inpatient psychotherapy. (3rd July 2016) - Reuter, Laurence; Munder, Thomas; Altmann, Uwe; Hartmann, Armin; Strauss, Bernhard; Scheidt, Carl Eduard
Abstract: Objective: Up to 50% of psychotherapeutic treatments end without significant improvements. While there is first evidence about predictors of nonresponse in outpatient psychotherapy, there are currently no studies investigating predictors of nonresponse in inpatient settings. Based upon a previous systematic literature review, we analyzed the predictive value of initial patient characteristics on nonresponse in symptom distress.Methods: Treatment episodes from 546 patients, treated for at least 4 weeks, were assessed under naturalistic conditions. Nonresponse status (i.e., lack of a reliable improvement in symptom distress) was investigated at four different time points: at week 4, at discharge, and at a two follow-ups (3 and 12 months after discharge). Hierarchical binary logistic regression models were used to predict nonresponse. Sociodemographic data, clinical variables, and the previous response status were entered subsequently in the model.Results: A moderate or functional level of initial symptom distress, a comorbid personality disorder, and previous nonresponse were the most consistent predictors of nonresponse.Conclusions: The results point to the importance of early outcome assessment and suggest the implementation of more symptom-specific treatments.